Enrichment and determination of sixteen trace polycyclic aromatic hydrocarbons in barbecue smoke by using a continuous magnetic solid‐phase extraction and gas chromatography‐mass spectrometry. Issue 1 (13th January 2020) - Pan, Yan; Zhang, Yanhao; Peng, Zifang; Ba, Xin; Zhao, Wuduo; Li, Xinglin; Guo, Yun; Ouyang, Gangfeng; Zhang, Shusheng; Zhang, Bin
Abstract: In this study, an innovative approach is proposed to predict the contribution of sixteen polycyclic aromatic hydrocarbons in barbecue smoke based on magnetic solid‐phase extraction system and gas chromatography‐mass spectrometry. In order to improve the detection limit of gas chromatography‐mass spectrometry, a kinds of magnetic nanomaterial synthesized previously was used as a sorbent in magnetic solid‐phase extraction. The recoveries ranged from 73.4% to 90.7%, and the limits of detection and limits of quantification were in the range 1.2‐5.4 ng·L −1 and 3.7‐16.4 ng·L −1 respectively. The method was successfully applied to the analysis of polycyclic aromatic hydrocarbons in smoke of the pork belly. The developed method could be potentially used for the assessing of polycyclic aromatic hydrocarbons profiles in environment pollution.